The hemisphere of fear: the presence of sharks influences the three dimensional behaviour of large mesopredators in a coral reef ecosystem. Issue 5 (1st March 2020) - Lester, Emily K.; Langlois, Tim J.; Simpson, Stephen D.; McCormick, Mark I.; Meekan, Mark G.
Abstract : Predators can exert strong ecological effects on their prey either via consumption or by altering their behaviour and morphology. In marine systems, predators and their prey co‐occur in a three‐dimensional environment, but to date predator–prey studies have largely focussed on behaviours of prey on horizontal (distance from shelter) rather than vertical (height in water column) axes. We used life‐size shape‐models of a blacktip reef shark Carcharhinus melanopterus (threatening shape‐model), a juvenile coral trout Plectropomus leopardus (non‐threatening shape‐model) and a shape‐control to examine the impact of perceived instantaneous (measured by time to first feeding) versus sustained (measured by time to consume the entire bait) predation threats on the feeding behaviour and three‐dimensional use of space by mesopredatory reef fishes in a coral reef environment. We found that mesopredatory fishes such as red snapper Lutjanus bohar and spangled emperor Lethrinus nebulosus took longer to begin feeding and to consume predation assays (fish baits) at greater distances from the shelter of a patch reef across both horizontal and vertical axes and that this phenomenon was stronger in the vertical axis than the horizontal. The presence of a life‐size shape‐model of a shark, which we used to increase the perception of predator threat, magnified the instantaneous effect compared to non‐threatening models, but not the sustained effect. We found no evidence for a difference in the level of predation risk posed by the shape‐model of the juvenile coral trout (a non‐threatening reef fish) and a negative control (no shape‐model). Our study suggests that mesopredators modify their behaviours in response to the perceived risk of predation across both horizontal and vertical axes away from shelter, and that this response is most severe on the vertical axis, potentially limiting daytime foraging behaviour to a hemisphere around shelter sites.